Post Partum Midwifery Care For Mrs. “L” P1A0 Second Day With Breast Milk - Asmiati; Jeni Samrida, Wa Ode Nesya; Sitti Justin, Wa Ode (International Journal of Multidisciplinary Learners, 2025)
Background :Damaged breast milk is a condition in which venous and lymphatic flow is obstructed, disrupting the circulation of the mother's milk, increasing pressure on the milk ducts and alveoli. This condition is generally caused by a buildup of milk that is not released, resulting in a blockage. Objective: midwifery care is to provide comprehensive pregnancy care for Mrs. "L" PIA0 with the problem of breast milk dams at the Bataraguru Community Health Center. The research method uses a case study approach by applying Varney's seven-step management protocol, with data collection from primary and secondary sources. Researchers carry out midwifery care based on Varney's management steps: basic data identification, actual problem/diagnosis identification, potential problem/diagnosis identification, immediate action/collaboration, action planning, implementation, and evaluation. The results of research on Mrs. “L” indicates a breast milk dam problem confirmed by history, physical examination, and temperature measurement of 38°C. Documentation of all findings and actions in the care process is essential for legal accountability and compliance. This study recommends increasing research time and improving the skills and competence of health workers, especially midwives, in providing more specialist health services. Conclusion already given as much as possible and in accordance with standard midwifery services/care plans and complications that may occur can be resolved.